Recurrent hypoglycemia in Diabetes Type 1: a case report - Martinotti, Irene; Cirla, Piero Emanuele (La Medicina del Lavoro, 2020)
Introduction: Insulin as diabetes therapy, if not well accepted by the patient, can worsen life quality and lead to compromised glucose control. Diabetic emergencies, such as hypoglycemia, can occur. According to social responsibility, corporate actions plays a relevant role in supporting the well-being of diabetic workers. Objectives: To report a case of management of severe recurrent hypoglycemic crises. Results: An advanced tertiary sector office worker (health risks: VDU, organization and stress, no company car use), suffering from Diabetes Type 1 with recurrent severe hypoglycemic crisis during the working time was brought to the attention of the occupational physician. The patient was followed by a high-level specialized diabetic center, but an unusual personality and bizarre ideas on self-regulation of diabetes resulted in rejection of continuous infusion with insulin pump in favor of multiple daily insulin injections therapy. Discussion: Advanced tertiary sector, characterized by a space-time expansion of the working time, didn’t facilitate acceptance of the regularity in insulin therapy and meals. Company prevention system intervention is useful to achieve a satisfactory balance: social support, availability of a refrigerator for medicines and an infusion pump. Conclusions: A constructive action of the “company system” can be useful to provide effective support in the management of diabetic therapy, with real positive implications on health status.